Multiproxy investigation of the last 2,000 years BP marine paleoenvironmental record along the western Spitsbergen margin - Fiorenza Torricella; Viviana Maria Gamboa Sojo; Karen Gariboldi; Nessim Douss; Maria Elena Musco; Chiara Caricchi; Renata Giulia Lucchi; Katia Carbonara; Caterina Morigi (Arctic, Antarctic, and Alpine Research, 2022)
A reconstruction of the last 2,000 years BP of environmental and oceanographic changes on the western margin of Spitsbergen was performed using a multidisciplinary approach including the fossil assemblages of diatoms, planktic and benthic foraminifera and calcareous nannofossils and the use of geochemistry (X-ray fluorescence spectroscopy, X-ray diffraction). We identified two warm periods (2,000–1,600 years BP and 1,300–700 years BP) that were associated with the Roman Warm Period and the Medieval Warm Period that alternate with colder oceanic conditions and sea ice coverage occurred during the Dark Ages (1,600–1,300 years BP) and the beginning of the Little Ice Age. During the Medieval Warm Period the occurrence of ice-rafted debris and Aulocoseira spp., a specific diatom genus commonly associated with continental freshwater, suggests significant runoff of meltwaters from local glaciers.